Constitutional Protection of the Right to Sustainable Development ( A Comparative Study ) - Ali Jasim Mezher; Samira Ghasi Ajel; Layali Rahi Ajmi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The concept of sustainable development, despite its increasing frequency in international law literature, is too vague to be clearly defined and implemented. The concept of sustainable development appears in various documents withdifferent, even competing, themes and scopes. Rather than being a simultaneous manifestation of three dimensions: economic, social, and environmental, it is essentially an economic and environmental concept, and economic development is the primary priority for all countries, both developed and developing. By failing to fulfill their obligations to developing countries, developed countries have created an atmosphere of mistrust in establishing global sustainable development platforms. Overall, it appears that although the concept and idea of ​​sustainable development have gained widespread acceptance in international legal literature, and significant efforts have been made to assess the achievement of sustainable development, the unity of the three areas of economic development, social development, and environmental protection still faces challenges. There is a significant gap regarding the theoretical and practical position of sustainable development on the international stage and within the framework of international development law. The importance of this research lies in analyzing the constitutional protection of the right to sustainable development in the Iraqi Constitution and its compatibility with international standards. It also examines the legal and practical challenges facing Iraq, Egypt, and Jordan in implementing this right on the ground, and reviews the role of 2 governmental institutions and civil society in promoting and protecting the right to sustainable development.